Biophysical and Biochemical Markers of Metal/Metalloid-Impacts in Salt Marsh Halophytes and Their Implications - Anjum, Naser A.; Duarte, Bernardo; Caçador, Isabel; Sleimi, Noomene; Duarte, Armando C.; Pereira, Eduarda (Frontiers in Environmental Science, 2016)
As a major sink, estuarine/salt marsh ecosystem can receive discharges laden with myriads of contaminants including metals/metalloids from man-made activities. Two among the major consequences of metal/metalloid-exposure in estuarine/salt marsh ecosystem flora such as halophytic plants are: (a) the excessive accumulation of light energy that in turn leads to severe impairments in the photosystem II (PS II), and (b) metal/metalloids-accrued elevation in the cellular reactive oxygen species (ROS) that causes imbalance in the cellular redox homeostasis. On one hand, plants adopt several strategies to dissipate excessive energy hence eventually to avoid damage in the PS II and maintain optimum photosynthesis. On the other hand, components of the cellular redox system quickly respond to metal/metalloid-exposure, where plants try to maintain a fine-tuning among these components, and tightly control the level of ROS and its potential consequences. Herein, major insights into, and the significance and implications of important biophysical and biochemical markers in metal/metalloid-exposed halophytes are overviewed and also highlighted main aspects so far least explored in the present context. Discussion advocates to regularly monitor and integrate studies on the highlighted herein biophysical and biochemical markers taking into account the missing aspects such as essential and non-essential metal/metalloid-speciation, -availability, and -methylation, role of the obvious microbial activities, and a comparative account of the outcomes of the studies on mixture of metal/metalloid performed in laboratory and field conditions. Thus, consideration of these missing aspects in future studies on the subject can help us to: (a) unveil the status of the metal/metalloid-contamination and -impact; (b) understand adaptive responses of salt marsh halophyte to metals/metalloids, and also (c) to devise sustainable strategies for the environmental or ecosystem management and safety.